EXODUS EXPERIENCE: Language and Truth - Edayadiyil, George (Journal of Dharma, 2010)
The Exodus experience is at the heart of the Hebrew Bible and further it is one of the greatest biblical paradigms. In the ancient world there was no distinction between the cultic aspects of the worship of the gods and the social activities of the state. It is the Greco-Roman world that made such a distinction.1 In Hebrew religion there was never a separation between the secular history and the religious history of salvation. Liberation has always been experienced in Israel as a historical reality which nevertheless is primarily and profoundly religious in character.2 In the Indian religions, too, we do not find such a separation. Today this distinction is evident in most of the contemporary societies where each recognizes the role of the other, even though the temptation to dictate terms for the other is quite evident.